The effects of sport-specific drills training or high-intensity interval training in young tennis players - Fernandez-Fernandez, J.; Sanz, D.; Sarabia, J. M.; Moya, M. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To compare the effects of combining high-intensity training (HIT) and sport-specific drill training (MT) versus sportspecific drill training alone (DT) on fitness performance characteristics in young tennis players.